Study on mining-induced stress behavior on surrounding rock of rockburst mine under large buried depth and hard overburden - Xingen Ma; Bing Hu; Eryu Wang; Qiangdi Geng; Zhiwen Liu; Yongyuan Li; Fulong Sun; Bingshan Wang; Wei Wang (Scientific Reports)
Abstract Xinzhuang Coal Mine in Huaneng Qingyang Mining Area has geological characteristics such as large buried depth, thick topsoil and hard overburden, which is a typical kilometer-deep rockburst mine.Currently, the mine remains in the fundamental construction phase. This provides a theoretical foundation for the mine’s subsequent production processes. , this paper studies the stress distribution law of surrounding rock in the stope of Xinzhuang Coal Mine. First of all, select the Panel 1 west wing of Coal 8 as a typical representative, and establish a large three-dimensional refined numerical model. Then, through numerical simulation research, the characteristics of surrounding rock abutment stress distribution zone in the mining process of the working face under complex conditions are obtained, which provides support for the regional design of rockburst prevention and control. The main research conclusions are as follows: (1) The research reveals the distribution characteristics of mining stress, elastic energy accumulation, and plastic zone at different widths of the first mining face, and determines the reasonable width of the working face. It is considered that the width of the working face can be greater than 175 m and less than 250 m, and the design width 200 m of the working face of Xinzhuang Coal Mine is reasonable. (2) The research reveals the evolution law and influence factors of mining stress, elastic energy accumulation and plastic zone distribution in the first mining face. The research results can not only provide theoretical support for the subsequent production of Xinzhuang Coal Mine, but also provide reference for the rockburst prevention and control work of mines with similar geological conditions.